THE DEVELOPMENT OF COHERENT SPEECH OF PRESCHOOL CHILDREN WITH SPEECH DISORDERS IN THE PROCESS OF COGNITIVE DEVELOPMENT ACTIVITIES - V. Khmelkova, E.; B. Bashmakova, S.; G. Lukovenko, T.; Yu. Dobromil, Y.; E. Fedotova, A. (Revista Gênero e Interdisciplinaridade, 2020)
At the present stage of development of defectological science and practice, the problem of speech correction of children with disabilities, in particular preschool children with General underdevelopment of speech (GUS) has a great scientific and practical importance. The overcoming of speech disorders and the ability to choose an educational route determine the need of the organization and determination of the content of targeted comprehensive speech therapy assistance. The article scientifically justifies the possibility of using cognitive research activities to improve the performance of speech development of children with disabilities. The efficiency of the program of development of coherent speech of preschool children with General underdevelopment of speech in cognitive research activity is experimentally proved. It is clearly shown that the inclusion of preschool children with General underdevelopment in the educational and research activities promotes the formation and development of skills of making coherent statements: phrases and sentences of the story on the demonstrated actions, story description, story based on personal experience.